PERBEDAAN KEPATUHAN MINUM OBAT PADA PASIEN YANG BARU TERDIAGNOSA DAN SUDAH LAMA TERDIAGNOSA PENYAKIT DIABETES MELITUS TIPE 2 - Selly Septi Fandinata; Rizky Darmawan (Jurnal Ilmiah Manuntung, 2020)
Diabetes mellitus is a chronic disease caused by insufficient insulin effectively. Compliance medication in patients diabetes mellitus is important to achieve treatment goals and effective to prevent complications in diabetes mellitus. The duration of suffering from DM is one of the factors that influences medication adherence. The purpose of this study is to compare the differences in adherence to taking medication between patients who have just been diagnosed with diabetes mellitus type II. Questionnaire instrument 4 indicators of compliance (right dose, right frequency, right interval, right time). Analysis statistical of the Mann-Whitney test. Total of 10 new patients and 20 old patients were diagnosed. The results study is patient to be compliant with right dose adherence 8 new patients (80%), 19 old patients (95%). Right frequency adherence 9 new patients (80%), 19 old patients (95%). Timely compliance 7 new patients (70%), 16 old patients (80%). Right interval adherence 4 new patients (40%), 13 old patients (65%). The results of data analysis showed p-value = 0.076> 0.05 there was no significant difference in adherence to taking medication between old patients and new patients with diabetes mellitus type II.